Electrocoagulation Method Using Al/Graphite Electrode for Removal Surfactant LAS (Linear Alkylbenzene Sulfonate) - Nafisa Khairunisa; Suhartana Suhartana; Damar Nurwahyu Bima (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
An increasing number of laundries have caused water contamination by surfactants. One commonly used surfactant is LAS (Linear Alkylbenzene Sulfonate), a material difficult to decompose, polluting the environment. Electrocoagulation was carried out using Al/Graphite electrode, applied to LAS surfactant artistic waste. This study aims to determine the functional ability of the Al/Graphite electrode in reducing surfactant through electrocoagulation. Various variations were carried out, on the voltage parameters (3,6,9,12) Volt; NaCl concentration (0;0.4;0.8;1.2;1.6;2) g/L; pH (3,5,7,9,11) and time (10,20,30,40,50) minutes. To analyze the changes in the sample before and after electrocoagulation, characterization was carried out using a UV-VIS spectrophotometer and FTIR. A kinetic study was conducted to determine the reaction order of electrocoagulation surfactant. Based on a study, removal at condition voltage 9 Volt, initial pH of the solution 9, electrocoagulation time 50 minute, and the addition of NaCl electrolyte 2 g/L, obtained surfactant concentration was 0,785 mg/L with removal efficiency 97,45%. UV-VIS spectra show a decreased absorption at a wavelength of 653 nm. FTIR spectra showed the presence of absorption on the same functional groups, which indicated that most of the surfactant pollutants could be separated from the wastewater through the electrocoagulation process. The second-order reaction was obtained in the surfactant electrocoagulation process.